Assessment, validation and deployment strategy of a two‐barcode protocol for facile genotyping of duckweed species1. (12th August 2014) - Borisjuk, N.; Chu, P.; Gutierrez, R.; Zhang, H.; Acosta, K.; Friesen, N.; Sree, K. S.; Garcia, C.; Appenroth, K. J.; Lam, E.
Abstract: Lemnaceae, commonly called duckweeds, comprise a diverse group of floating aquatic plants that have previously been classified into 37 species based on morphological and physiological criteria. In addition to their unique evolutionary position among angiosperms and their applications in biomonitoring, the potential of duckweeds as a novel sustainable crop for fuel and feed has recently increased interest in the study of their biodiversity and systematics. However, due to their small size and abbreviated structure, accurate typing of duckweeds based on morphology can be challenging. In the past decade, attempts to employ molecular barcoding techniques for species assignment have produced promising results; however, they have yet to be codified into a simple and quantitative protocol. A study that compiles and compares the barcode sequences within all known species of this family would help to establish the fidelity and limits of this DNA‐based approach. In this work, we compared the level of conservation between over 100 strains of duckweed for two intergenic barcode sequences derived from the plastid genome. By using over 300 sequences publicly available in the NCBI database, we determined the utility of each of these two barcodes for duckweed species identification. Through sequencing of these barcodes from additional accessions, 30 of the 37 known species of duckweed could be identified with varying levels of confidence using this approach. From our analyses using this reference dataset, we also confirmed two instances where mis‐assignment of species has likely occurred. Potential strategies for further improving the scope of this technology are discussed.